2003
DOI: 10.1097/00005537-200311000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Retronasal olfactory function in nasal polyposis

Abstract: Better retronasal than orthonasal olfactory function seems to be associated with the presence of mechanical obstruction in the anterior portion of the olfactory cleft. In turn, these data indicate that olfactory loss in NP seems to be caused by regional mechanical or inflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 19 publications
2
59
3
3
Order By: Relevance
“…First, in accordance with the literature, our study demonstrated a significant correlation between TS and olfactory function . This relation between TS and olfaction could be a potential confounding source of TS performance in CRS, because patients with CRS generally suffer from hyposmia or anosmia . This is not applicable to our findings, however, as CRS patients performed equally to controls on olfactory identification testing.…”
Section: Discussionmentioning
confidence: 99%
“…First, in accordance with the literature, our study demonstrated a significant correlation between TS and olfactory function . This relation between TS and olfaction could be a potential confounding source of TS performance in CRS, because patients with CRS generally suffer from hyposmia or anosmia . This is not applicable to our findings, however, as CRS patients performed equally to controls on olfactory identification testing.…”
Section: Discussionmentioning
confidence: 99%
“…From a list of each four items, the participants had to identify each odour using a forced choice paradigm. In the healthy population a mean score of 8.5 is achieved [20]. A score beyond 7 indicates impaired function.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…The scores in between are considered to reflect hyposmia. Patients 1 and 2 underwent further retronasal olfactory testing [13,14] and patient 1 underwent assessment of chemosensory event-related potentials [15].…”
Section: Olfactory Testingmentioning
confidence: 99%